Does Company Size and Profitability Matter? Investigating the Moderating Effects of Growth in Cash Flow on Stock Performance - Agus Fuadi; Dian Sulistyorini Wulandari; Fedia Chairunnisa (Journal of Scientific Interdisciplinary, 2024)
This research examines the intricate relationships between company size, growth in cash flow, and stock performance, revealing complexities that challenge traditional financial analysis. While company size is often associated with stable stock performance due to advantages such as economies of scale and market power, the findings indicate that size alone does not positively impact stock performance. Furthermore, the study demonstrates that growth in cash flow does not significantly moderate the relationship between company size and stock performance. This suggests that external factors, such as regulatory changes or market sentiment, may play a more decisive role. The results underscore that cash flow, while an important indicator of financial health, does not enhance the influence of company size on stock performance, particularly in certain industries where external conditions prevail. This underscores the need for a more comprehensive evaluation approach that considers a broader range of factors when assessing stock performance. It's time to move beyond traditional metrics like profitability and cash flow growth and equip ourselves with a more robust set of tools for analysis. Ultimately, this research advocates for a multifactorial approach to stock performance evaluation, emphasizing the importance of understanding the interplay between various variables, including industry trends and macroeconomic conditions. By adopting this comprehensive perspective, investors and analysts can make more informed decisions and strategies, enhancing their ability to navigate the complexities of the financial markets.